Real-Time Dissecting the Entry and Intracellular Dynamics of Single Reovirus Particle - Liu, Jia; Yu, Cong; Gui, Jian-Fang; Pang, Dai-Wen; Zhang, Qi-Ya (Frontiers in Microbiology, 2018)
Reoviruses are non-enveloped viruses with wide host range, can cause infections in animals, plants and microorganism. Tracing the journey and elucidating the details in viral infection process are crucial for understanding the pathogenic mechanism. Here, we used quantum dots-based single particle tracking technology combined with gene markers, biochemical assays and ultrastructural observation to reveal unobservable infection steps and map dynamic interactions between a reovirus, Scophthalmus maximus reovirus (SMReV), and its host cell in real time. The results showed that the single membrane-bound reovirus particle can enter into the cell within 13s through nascent clathrin-caoted pits, and most of the particles could internalize into cytoplasm within 30 min postinfection. The specific inhibitors analysis also showed that entry of SMREV depended on clathrin-mediated endocytosis rather than cavolin-mediated endocytosis and micropinocytosis. The motion analysis of internalized single particle indicated that the reovirus moved slowly in the actin-enriched cell periphery, while it moved relatively faster toward the cell interior. And the apparent upward curvature of mean square displacement-time interval plots was fitting with an equation of MSD = 4D∆t + (Vt)2, which also indicated the movement experienced a directed motion dependence on the cytoskeleton. Further, dual-labelling of virus and cytoskeleton demonstrated that internalized SMReV transport was dependent first on actin filaments at the cell periphery, and then on microtubules towards the cell interior. Then visualization of SMReV trafficking in the endosomes revealed that the internalized reovirus particles were sorted from early endosomes to late endosomes, then part of them were delivered to lysosome. This study for the first time revealed intracellular dynamic and following the infection fate of fish reovirus in host cell in real time and in situ, which provided new insights into the infection mechanism of non-enveloped viruses.